Internet technologies and information services - Miller, Joseph B., 1952- (Santa Barbara, California : Libraries Unlimited, an Imprint of ABC-CLIO, LLC, 2014)
"The Internet has enabled the convergence of all things information-related. This book provides essential, foundational knowledge of the application of Internet and web technologies in the information and library professions"--
PART I: INTERNET TECHNOLOGIES -- Chapter 1: Introduction Chapter 2: The World Wide Web -- Chapter 3: Networks and Connection Technologies -- Chapter 4: Internet Technologies: TCP / IP -- Chapter 5: Higher-Level Internet Protocols: Making the Internet Work -- Chapter 6: Internet-Connected Devices and Security -- PART II: BUILDING THE WEB -- Chapter 7: Web Design and Graphics -- Chapter 8: Web Publishing with the Hypertext Markup Language -- Chapter 9: Controlling Presentation with Styles -- Chapter 10: Introduction to Web Programming -- Chapter 11: Web Technologies and Content Management -- Chapter 12: XML Primer -- PART III: INTERNET CONTENT AND INFORMATION RETRIEVAL -- Chapter 13: Internet Content -- Chapter 14: Information Retrieval -- Chapter 15: Internet Search -- Chapter 16: Libraries and the Internet: Learning from the Past, Exploring the Future
Includes bibliographical references (pages 455-478) and index.
Keywords: Libraries and the Internet; Libraries -- Information technology; LANGUAGE ARTS & DISCIPLINES / Library & Information Science / General; LANGUAGE ARTS & DISCIPLINES / Study & Teaching